Efektifitas Penegakan Hukum Terhadap Eksploitasi Sumber Daya Perikanan Di Zona Ekonomi Eksklusif Ditinjau Dari Undang-Undang Nomor 5 Tahun 1983 - Reinier Sukarnolus Dimitri Sitanala (SASI, 2018)
Indonesia as a coastal country has the right to have the right to do business and exploitation and conservation and management of natural and non-biological natural resources in the Indonesian Exclusive Economic Zone. The obligation to carry out conservation of living natural resources is to determine the amount of catch allowed and determine the limits of sustainable harvests which aim to promote the utilization of the natural resources contained in the Indonesian Exclusive Economic Zone. To find out the implementation of the provisions in the 1982 Sea Law Convention on Exclusive Economic Zones in Indonesian legislation, it is associated with licensing, where licensing can be carried out through utilization so as not to exceed available limits. In addition, it is also the implementation of law enforcement for foreign fishing vessels that violate fisheries provisions in the view of international law and national law in the Exclusive Economic Zone